2005
DOI: 10.1111/j.1601-0825.2005.01142.x
|View full text |Cite
|
Sign up to set email alerts
|

Number V Oral lichen planus: clinical features and management

Abstract: Oral lichen planus (OLP) is a relatively common chronic inflammatory disorder affecting stratified squamous epithelia. Whereas in the majority of instances, cutaneous lesions of lichen planus (LP) are self-limiting and cause itching, oral lesions in OLP are chronic, rarely undergo spontaneous remission, are potentially premalignant and are often a source of morbidity. Current data suggest that OLP is a T cell-mediated autoimmune disease in which auto-cytotoxic CD8+ T cells trigger apoptosis of oral epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
354
2
51

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 394 publications
(437 citation statements)
references
References 143 publications
8
354
2
51
Order By: Relevance
“…One possible explanation for this difference is that, routinely, more women (64.5%) than men (35.5%) come to our clinic for a diagnosis of some type oral mu- (3,9,17). Two studies have shown a complete identification of NSAIDs as LDR inducers, with case history strongly suggesting a relationship between NSAID intake and the onset of OLP, with complete resolution or marked improvement of the lesions when these drugs were withdrawn as well as recurrence when patients were again given the offending drug (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…One possible explanation for this difference is that, routinely, more women (64.5%) than men (35.5%) come to our clinic for a diagnosis of some type oral mu- (3,9,17). Two studies have shown a complete identification of NSAIDs as LDR inducers, with case history strongly suggesting a relationship between NSAID intake and the onset of OLP, with complete resolution or marked improvement of the lesions when these drugs were withdrawn as well as recurrence when patients were again given the offending drug (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…OLP is difficult to palliate and in several cases, most therapies are merely symptomatic [2]; even if the best treatment remains high-potency topical corticosteroids, management is usually empirical, without adequate control groups or corrected study designs [3].…”
Section: Introductionmentioning
confidence: 99%
“…OLRs are often seen in direct topographic relation to the offending agent and are generally unilateral, and they can be reticular, in the form of plaques, atrophic and erosive or a combination of the foregoing. However, classical OLP presents as bilateral and symmetrical, white, papular/reticular or red atrophic/ulcerative lesions affecting all areas of the oral mucosa [12][13][14]. The possible etiologic factors of OLP include genetic background, infectious agents, autoimmune reactions, immunodeficiency, chronic liver disease, drugs, chemicals, stress, trauma, food allergies, diabetes, hypertension, malignant neoplasms, electrogalvanism and dental materials [15,16].…”
Section: Introductionmentioning
confidence: 99%